The Potency of Ficus deltoidei Jack Bioactive as An Antidiabetic Treament: In Silico Study - Wahyurini, Dyahati; Clarinta Putri, Rizky; Wardani Hakim, Rani; Wibowo, Heri (Brawijaya University, 2024)
Background: Type 2 Diabetes Mellitus (T2DM) is a metabolic disease with an increasing prevalence. T2DM is related to chronic low-grade inflammation or meta-inflammation conditions. Nowadays, treatment begins to target the molecules or proteins involved in T2DM. Peroxisome Proliferator Activator Receptor gamma (PPAR-γ) is one of the proteins involved in T2DM. The Herbal is a potential solution to finding molecular medicine with bioactive compounds. Extract from Tabat Barito (Ficus deltoidea Jack) has proven as antidiabetic. It has many bioactive compounds and can be analyzed using software and molecular docking. This research aims to analyze the biological and pharmacological bioactive compounds of Ficus deltoidea Jack as an antidiabetic. Methods: The bioactive compounds of Ficus deltoidea Jack were determined from the literature. PASS (Prediction of Activity Spectra for Substances) was used to analyze the bioactive compounds. SwissADME was used to know the pharmacology properties Molecular docking was used to find the interaction between bioactive compounds and PPAR-γ. Results: Ficus deltoidea Jack has many bioactive compounds. Lupeol, Vitexin, and Isovitexin were chosen to advance analysis using PASS and SwissADME. All of them had antidiabetic activity. SwissADME was used to identify the pharmacology properties. The result, every bioactive compound has its specific characteristics. Molecular docking showed that Vitexin is the best, with ΔGibbs - 6.59kcal/mol and Inhibition constant (Ki) 14.77 µM. Conclusions: Ficus deltoidea Jack consists of many bioactive compounds. Vitexin and Isovitexin are potential as an antidiabetic. From the docking results, the strongest interaction is Vitexin.